2000
DOI: 10.2741/a563
|View full text |Cite
|
Sign up to set email alerts
|

Lipoperoxidation damage of spermatozoa polyunsaturated fatty acids PUFA scavenger mechanisms and possible scavenger therapies

Abstract: The lipid metabolism in sperm cells is important both as one of the main sources for energy production and for cell structure. The double leaflets of the membrane should be considered not simply as a passive lipid film, but as a very specialized structure. The complete maturation of the sperm cell membrane is attained after testicular lipid biosynthetic processes and after passage through the epididymis. A special composition of membrane phospholipids, rich in polyunsaturated fatty acids (PUFA), and the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 48 publications
2
35
0
5
Order By: Relevance
“…It has been shown that cells contain relatively large amount of PUFAs, and that their distribution is not homogeneous among cell populations. Moreover, a broad change in lipid repartition between the residual body and the spermatozoan cytoplasmic membrane has been described in the literature (Retterstol et al, 2000;Lenzi et al, 2000). Within the seminiferous epithelium, Sertoli cells are very active in metabolizing PUFAs while isolated germ cells are inefficient in synthesizing 22:5n-6 and 22:6n-3 (Hurtado de Catalfo and de Gomez Dumm, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cells contain relatively large amount of PUFAs, and that their distribution is not homogeneous among cell populations. Moreover, a broad change in lipid repartition between the residual body and the spermatozoan cytoplasmic membrane has been described in the literature (Retterstol et al, 2000;Lenzi et al, 2000). Within the seminiferous epithelium, Sertoli cells are very active in metabolizing PUFAs while isolated germ cells are inefficient in synthesizing 22:5n-6 and 22:6n-3 (Hurtado de Catalfo and de Gomez Dumm, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, sperms have little cytoplasm and low antioxidant status, what makes them more susceptible to the effects of direct oxidative stress (Shefi & Turek 2006). The abundant concentration of PUFA and cholesterol present in the cellular membrane of mature sperms (Ko et al 2014, Mendeluk et al 2015 provides the necessary fluidity for the occurrence of the fusogenic events associated with the fertilization process (Nordberg & Arnér 2001); however, it also makes them more vulnerable to oxidative stress (Lenzi et al 2000). A high ROS production along with a reduction in the total antioxidant capacity (Tramer et al 1998) can impair the fluidity of the plasma membrane of the sperm and raise sperm DNA damage (Miyaoka & Esteves 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic metabolism of human sperm produces various reactive oxygen species (ROS), which are potentially harmful to the sperm plasma membrane with its high content of polyunsaturated fatty acids (1)(2)(3). There is growing evidence that lipid peroxida�lini�al Urology �lini�al Urology tion damage to the plasma membrane of spermatozoa plays an important role in the mechanism of male infertility (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%